Configuration of the instrumental tools for generation of text representations of object of the curated database - Yu. Ismailova, Larisa; V. Kosikov, Sergey (International Journal of Engineering and Technology, 2018)
The paper considers the problem of configuring the instrumental tools (a workbench) for generating textual representations of objects in the curated database. A formal (formalized) representation of a fragment of a natural language sufficient to describe the content of data- base objects is proposed. Based on the matching of the expressive means of the proposed language, taking into account the general archi- tecture of the comprehensive information system, the configuration of support tools is proposed. The configuration provides support to the procedures for manipulating formal descriptions, including the ability to process both formal and textual representation of database objects. The approach has been tested in the field of support to the implementation of best available technologies.Â Â